2020
DOI: 10.1183/13993003.00454-2020
|View full text |Cite
|
Sign up to set email alerts
|

Impact of body mass index on development of nontuberculous mycobacterial pulmonary disease

Abstract: The incidence and prevalence of nontuberculous mycobacterial pulmonary disease (NTM-PD) have been increasing worldwide. The risk of NTM-PD may be higher in undernourished populations. We tried to elucidate the impact of body mass index (BMI) and its change on development of NTM-PD in this study.We performed a retrospective cohort study including South Koreans age >40 years who underwent biennial National Health Insurance System (NHIS) health checkups in both 2005 and 2009 or 2006 and 2010. We monitored elig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 32 publications
2
20
0
Order By: Relevance
“…In our study, 66.3% of the patients newly diagnosed with MAC-PD were positive for anti-GPL-core IgA antibodies, which is comparable to the sensitivity reported in a previous review (Shibata et al, 2016). Furthermore, the clinical characteristics of the patients with MAC-PD in our study were consistent with those in previous reports (i.e., the patients were predominantly slim women with nodular bronchiectatic disease) (Prevots & Marras, 2015;Tan et al, 2018;Furuuchi et al, 2019;Kendall & Winthrop, 2013;Simons et al, 2011;Daley et al, 2020;Izumi et al, 2019;Song et al, 2021). Kitada et al reported that the antibody titers reflect the disease activity to some extent (Numata et al, 2015;Kitada et al, 2008;Kitada et al, 2005) and found a weak correlation between the antibody titer levels and the extent of the disease on chest computed tomography (CT) (Kitada et al, 2015;Kitada et al, 2007).…”
Section: Discussionsupporting
confidence: 90%
“…In our study, 66.3% of the patients newly diagnosed with MAC-PD were positive for anti-GPL-core IgA antibodies, which is comparable to the sensitivity reported in a previous review (Shibata et al, 2016). Furthermore, the clinical characteristics of the patients with MAC-PD in our study were consistent with those in previous reports (i.e., the patients were predominantly slim women with nodular bronchiectatic disease) (Prevots & Marras, 2015;Tan et al, 2018;Furuuchi et al, 2019;Kendall & Winthrop, 2013;Simons et al, 2011;Daley et al, 2020;Izumi et al, 2019;Song et al, 2021). Kitada et al reported that the antibody titers reflect the disease activity to some extent (Numata et al, 2015;Kitada et al, 2008;Kitada et al, 2005) and found a weak correlation between the antibody titer levels and the extent of the disease on chest computed tomography (CT) (Kitada et al, 2015;Kitada et al, 2007).…”
Section: Discussionsupporting
confidence: 90%
“…This study included BMI data in the multivariable analysis for mortality; to the best of our knowledge, no published studies have examined BMI prior to death in patients with NTM-PD. However, several studies have reported an association between weight loss and [12,13,[21][22][23]. In this study, patients with NTM-PD who required unscheduled hospitalization had remarkably low BMIs, the median being 17.5 kg/m 2 .…”
Section: Discussionmentioning
confidence: 63%
“…A study in mice suggested that E 2 may have a protective role against intracellular mycobacterial infection [ 44 ]. Additionally, low BMI has been associated with the development and severity of NTM-PD [ 45 ]. Taken together, female hormones and a low BMI are strongly associated with the development of NTM-PD, as well as with osteoporosis, and may have affected the high comorbidity of osteoporosis in the current study.…”
Section: Discussionmentioning
confidence: 99%